Investigations on the influence CuO doping on elastic properties of Li2SO4–MgO–P2O5 glass system by means of acoustic wave propagation. (May 2021) - Venkata Sekhar, A.; Kityk, A.V.; Jedryka, J.; Rakus, P.; Wojciechowski, A.; Siva Sesha Reddy, A.; Naga Raju, G.; Veeraiah, N.
Abstract: By measuring ultrasonic velocity in Li2 SO4 –MgO–P2 O5 :CuO glasses we have evaluated different elastic coefficients; the values of these coefficients exhibited an increasing trend with increase of CuO concentration. Such increase is attributed to increasing presence of copper ions in monovalent state that cross link with phosphate structural units. Such increased degree of augmentation is predicted to be responsible for the increased magnitude of ultrasonic velocities and hence elastic coefficients of the titled glasses. Highlights: Ultrasonic velocities in Li2 SO4 –MgO–P2 O5 :CuO glasses were measured. Elastic coefficients exhibited an increasing trend with increase of CuO content. Such increase is ascribed to increase of Cu + ions that cross link with PO4 units.